Coenzyme Q10 and Immune Function: An Overview - David Mantle; Robert A. Heaton; Iain P. Hargreaves (MDPI AG, 2021)
Coenzyme Q10 (CoQ10) has a number of important roles in the cell that are required for optimal functioning of the immune system. These include its essential role as an electron carrier in the mitochondrial respiratory chain, enabling the process of oxidative phosphorylation to occur with the concomitant production of ATP, together with its role as a potential lipid-soluble antioxidant, protecting the cell against free radical-induced oxidation. Furthermore, CoQ10 has also been reported to have an anti-inflammatory role via its ability to repress inflammatory gene expression. Recently, CoQ10 has also been reported to play an important function within the lysosome, an organelle central to the immune response. In view of the differing roles CoQ10 plays in the immune system, together with the reported ability of CoQ10 supplementation to improve the functioning of this system, the aim of this article is to review the current literature available on both the role of CoQ10 in human immune function and the effect of CoQ10 supplementation on this system.